Efficacy of Aqueous Extract of Pawpaw (Carica Papaya) Leaf in the Control of Coccidiosis in Chicken - Babalola, Peter Olufemi (2015)
The study investigated the potency of aqueous extract of pawpaw leaf compared with a conventional anticoccidial drug, sulphamethazine sodium, in the treatment of coccidial infection in chicken. This was necessitated by the need to get an effective, readily available and comparatively cheaper drug to control coccidiosis.